A novel convenient approach toward the fouling alleviation in membrane bioreactors using the combined methods of oxidation and coagulation. (February 2020) - Sabouhi, Mohammad; Torabian, Ali; Bozorg, Ali; Mehrdadi, Nasser
Graphical abstract: Highlights: A novel economic method introduced to prolong MBR operational life. Oxidation-flocculation methods were used to lower mixed liquor fouling propensity. Optimum dosages of additives were assessed to achieve highest MBR efficiency. The operating time of commercial membranes was increased for almost 4 times. Abstract: A combination of oxidation and coagulation pretreatment processes was used to reduce membrane fouling. NaOCl and FeCl3 were selected as conventional cheap additives to modify the mixed liquor and prolong the operation life of the membranes. Optimum dosages of 1.93 mg/L FeCl3 and 1.71 mg/L NaOCl were determined through batch experiments considering MLVSS/MLSS ratio, COD, and soluble microbial products removal. Identical studies but under flow condition were then conducted to assess MLSS, COD removal, ammonia removal, SMP, extracellular polymeric substances, zeta potential, mean particle size, and SVI. Experimental results implied that, although combination of NaOCl and FeCl3 was able to lower the mean particle size, the sludge settling properties were not negatively affected. Furthermore, by employing a commercial membrane, it was confirmed that the operating time of the membrane could be increased by 3.7 times when a combination of NaOCl and FeCl3 was used to modify the feed solution.